Novel Therapeutic Approaches in Connective Tissue Disease-Associated Interstitial Lung Disease - Mulcaire-Jones, Erica; Pugashetti, Janelle Vu; Oldham, Justin M.; Khanna, Dinesh (Seminars in Respiratory and Critical Care Medicine, 2024)
Connective tissue diseases (CTD) comprise a group of autoimmune diseases that can affect multiple organs in the body including the lungs. The most common form of pulmonary involvement is interstitial lung disease (ILD). CTD-associated ILD (CTD-ILD) can take one of several courses including nonprogressive, chronically progressive, or rapidly progressive. Chronically and rapidly progressive patterns are associated with increased mortality. Limited randomized controlled trial data are available for treatment of CTD-ILD, with most data coming from systemic sclerosis-related ILD. The current first-line treatment for all CTD-ILD is immunosuppression with consideration of antifibrotics, stem cell transplant, and lung transplant in progressive disease. In this article, we review data for ILD treatment options in systemic sclerosis, rheumatoid arthritis, myositis, and primary Sjögren's syndrome-related ILDs.
Keywords: connective tissue disease; interstitial lung disease; rheumatoid arthritis; systemic sclerosis; idiopathic inflammatory myositis; primary Sjögren's syndrome; treatment